Report of Meeting. The Eighteenth Debrecen–Katowice Winter Seminar on Functional Equations and Inequalities Hajdúszoboszló (Hungary), January 31–February 3, 2018 - AMSil, Redakcja (Annales Mathematicae Silesianae, 2018)
Report of Meeting. The Eighteenth Debrecen–Katowice Winter Seminar on Functional Equations and Inequalities Hajdúszoboszló (Hungary), January 31–February 3, 2018.